Pengaruh Kombinasi Pupuk Kandang Ayam dan Pupuk Anorganik terhadap Corganik, N-total, Nisbah C/N dan Bobot Segar Tanaman Sedap Malam (Polyanthes tuberosa L.) pada Typic Hapludults - Muhammad Ryan Natasaputra; Anni Yuniarti (Soilrens, 2017)
The research was conducted to determine the effect of chicken manure and anorganic fertilizer combination towards organic carbon, total N, C:N ratio, and fresh weight of tuberose (Polyanthes tuberose L.) on Typic Hapludults. The research design used was Randomized Block Design (RBD) with ten treatments and three replications. The results of this research showed that there was an increase on organic carbon, total N, C:N ratio, and fresh weight of tuberose from combination of chicken manure and inorganic fertilizer. Treatments of ½ dosage of chicken manure (40 g/polybag) + ½ dosage of anorganic fertilizer (Urea 1,5 g/polybag, SP-36 0,25 g/polybag, KCl 0,15 g/polybag) was the efficient combination increased the fresh weight of tuberose by 91,56 g/plant.Keywords : inorganic Fertilizer, chicken Manure, Fresh Weight, Tuberose